1991
DOI: 10.1099/0022-1317-72-7-1543
|View full text |Cite
|
Sign up to set email alerts
|

Expression of potyvirus coat protein in Escherichia coli and yeast and its assembly into virus-like particles

Abstract: When the full-length coat protein (CP) of the potyvirus, Johnsongrass mosaic virus (JGMV), was expressed in Escherichia coli or yeast, it assembled to form potyvirus-like particles. The particles were heterogeneous in length with a stacked-ring appearance and resembled JGMV particles in their flexuous morphology and width. This cell-free assembly system should permit analysis of the mechanisms of particle assembly and genome encapsidation. Two mutant forms of CP produced by site-directed mutagenesis failed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
54
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 17 publications
4
54
0
Order By: Relevance
“…In the mutant pTTQ19:CP m94D (Fig. 1), only the residue R TM was changed to D in contrast to the previously described double mutant pTTQ19:CP R-Q* (Jagadish et al, 1991) where both R TM and Q~9~ were mutated. This was done to eliminate any effects, in the new mutant pTTQ19:CP m94D, that might have been caused by the introduction of the amino acid residue L in place of Q195 adjacent to R TM.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…In the mutant pTTQ19:CP m94D (Fig. 1), only the residue R TM was changed to D in contrast to the previously described double mutant pTTQ19:CP R-Q* (Jagadish et al, 1991) where both R TM and Q~9~ were mutated. This was done to eliminate any effects, in the new mutant pTTQ19:CP m94D, that might have been caused by the introduction of the amino acid residue L in place of Q195 adjacent to R TM.…”
mentioning
confidence: 68%
“…We have used site-directed mutagenesis followed by expression of a modified Johnsongrass mosaic virus coat protein gene in Escherichia coli and electron microscopic analysis, to initiate identification of some of the residues within the core region crucial to self-polymerization. We have previously shown that complete coat protein synthesized in the yeast Saccharomyces cerevisiae, or with an additional 16 amino acids at its N terminus in E. coli, readily assembled to form potyvirus-like particles (Jagadish et al, 1991). These particles were similar in their morphology to those assembled in vitro in the absence of viral RNA (McDonald & Bancroft, 1977).…”
mentioning
confidence: 85%
See 3 more Smart Citations